Leaf anatomy of orchids micropropagated with different silicon concentrations - doi: 10.4025/actasciagron.v34i4.15062 - Soares, Joyce Dória Rodrigues; Pasqual, Moacir; Araujo, Aparecida Gomes de; Castro, Evaristo Mauro de; Pereira, Fabricio José; Braga, Francyane Tavares (Acta Scientiarum. Agronomy, 2012)
Research on anatomical modifications under in vitro culture is essential to the definition and understanding of the development of micropropagated plants. Likewise, such research is essential to improve the steps of the acclimatization process. Accordingly, the objective of the present study is to verify the differences in the leaves anatomical traits of micropropagated orchids under calcium silicate concentrations. Seedlings of in vitro-germinated seeds, measuring 0.5 cm in length, were inoculated in 250 cm3 pots with 60 mL MS culture medium and different silicon concentrations (0, 0.5, 1.0 and 2.0 mg L-1) in different culture environments (natural environment, in a greenhouse and an artificial environment in a growth chamber) and in all statistical combinations. The pH of the culture medium was fixed at 5.8 ± 0.1 and gelified with 5.5 g L-1 of agar before autoclaving at 121ºC and 1 atm for 20 min. After 150 days, an anatomical analysis was performed on cross-sections of the plant leaves. A complete randomized design was used. Modifications occurred on the plants of those treatments containing silicon compared to those without silicon, and between environment fo artificial and natural light. Plants showed larger growth at the artificial light treatment with 0.5 and 2.0 mg L-1 of calcium silicate respectively for the native and hybrid plants Treatments without silicate application induced chlorenchyma and epidermis deformation compared to silicon containing treatments, this effect can affect directly or indirectly plant growth at no silicon conditions.